Filsafat Hukum Sosiologis (Sosiological Jurisprudence); Konsep dan Aktualisasinya Dalam Hukum Indonesia - Rahmatullah, Indra (UIN Jakarta, 2021)
Critical Legal Studies (CLS) is an alternative thought in legal philosophy that can provide a different view of the law. The hallmark of this thinking is that it does not take the laws made by the state taken for granted before the process of critical reasoning struggles against its legal substance. There is a situation of distrust and concern that the laws made by the state cannot bring justice because the process goes through a tug-of-war struggle for political and economic interests, causing the legal product to be vulnerable to imperfections. Neutrality, and impartiality are the keywords that become indicators to purify the law. Therefore, CLS strives to always open the veil of power relations and economic relations which always interfere with the law with its own struggle and logic.